The Influence of Promotion and Physical Evidence on Purchasing Decisions at Wisma Sukapura Hotplate, Bandung Regency - Puteri, Alya Rachmatya; Jamiat, Nuslih (Journal of Advances in Accounting, Economics, and Management, 2024)
The basic human need for food is one of the factors that can support the growth of the culinary industry. Food presentation using a hotplate has become a trend that is very popular with the public in recent years. One of the hotplate business actors in Bandung Regency is Wisma Sukapura Hotplate, commonly known as WS Hotplate, which has a menu of chicken and beef steak dishes at affordable prices. WS Hotplate is in the campus area, especially Telkom University, so there is a decrease in income during the student holiday season. This study aims to determine in more detail the effect of promotion and physical evidence on purchasing decisions simultaneously and partially. This research uses quantitative methods and a series of tests such as the classical assumption test, which includes normality, multicollinearity, and homoscedasticity tests; multiple linear regression analysis tests; hypothesis testing, which provides for partial (t) and simultaneous (f) tests; and the coefficient of determination test. The non-probability sampling technique used is purposive sampling. The population of people domiciled in Bandung Regency who have purchased at WS Hotplate is unknown, with a sample of 100 respondents. Data testing in research using statistics, namely SPSS, shows that the results of this study are promotional variables and physical evidence that have a significant influence both partially and simultaneously on purchasing decisions at Wisma Sukapura Hotplate, Bandung Regency.